Bibliotherapy: A "new" service for Libraries - Giannakopoulou, Fani; Antoniou, Angeliki; Vraimaki, Eftychia; Maniadaki, Katerina (Journal of Integrated Information Management, 2024)
Purpose - The present research aims to investigate the nature and characteristics of bibliotherapy, as they have been formulated in experts’ opinions related to the specific topic. The research aimed to set a general framework and to examine the relationship between bibliotherapy and librarians. Design / methodology / approach - The generic purposive sampling technique was used to investigate the topic. Six in-depth semi-structured interviews were conducted. Interview data were analyzed, and 5 distinct categories emerged. Findings – Participants believe that books can be used to treat psychological problems and difficulties and improve the quality of life of individuals. Thus, bibliotherapy can be viewed as an opportunity for libraries to strengthen their position in modern societies and offer new, relevant services. Originality / value - The paper presents the views of six experts (three from Greece, one from Italy and two from the UK). Two of them were approached due to their direct professional involvement with bibliotherapy. The remaining participants are connected in various ways to books and reading and have a good insight into the therapeutic potential of books.